The Role of Internal Firm Processes and Structures in the Income Inequality Formation - Игорь Сергеевич Чириков (Journal of Economic Sociology, 2010)
The paper deals with the different characteristics of organization and internal organizational processes that influence the income inequality formation. On the basis of the existing studies we found out that a number of organization’s characteristics (its size, growth, demographic characteristics, used technologies, trade unions and external environment) have direct impact on career mechanism and wage setting. Applying thesis by Granovetter about social embededness of economic action to the assessments and actions for career mobility within the firm give us the opportunity to understand better that logic of hierarchical functions, selection mechanisms and wage setting.